Answer:
peter = $54
jane = $36
Explanation:
let peter = x
let jane = y
peter + jane = $90
x+y = 90 --------- (1)
peter gave jane $16 = x-16
jane gets extra $16 from peter = y+16
peter would have $14 less than jane
jane - peter = $14
(y+16)-(x-16) = 14
y+16-x+16 = 14
y-x+32 = 14
y-x = 14-32
y-x = -18 ---------- (2)
x+y = 90 --------- (1)
y-x = -18 --------- (2)
from (1)
x+y = 90
y = 90-x --------- (3)
substitute (3) into (2)
y-x = -18
90-x-x = -18
90-2x = -18
-2x = -18-90
-2x = -108
x = 54
substitute x = 54 into (3)
y = 90-x
y = 90-54
y = 36
x = peter = $54
y = jane = $36